Fundamental factors of economic growth in post-socialist transformation countries - Miłaszewicz, Danuta (Ekonomia i Prawo. Economics and Law, 2021)
Motivation: Economic growth is the product of many interrelated shallow and deep (fundamental) determinants. The deep ones include the geographical conditions of development, institutional conditions and the openness of the economy. Research on the impact of fundamental factors on economic growth and their importance were carried out for various groups of countries, primarily developing as well as developed ones. Aim: The study continued the analysis of the fundamental factors of economic growth in selected transition countries carried out in 2010. The focus was on determining the changes that have occurred over time in the area of fundamental determinants of growth in order to perform a comparative time analysis after the next decade of functioning of these countries. Results: The analysis shows that the geographical factors that formed one of the elements of the initial conditions turned out to be important for the analysed economies. Institutions are also very important, and the change in their quality in the analysed period was the smallest in the group of the poorest countries.